Destruction of composite materials with two parallel coaxial cracks at the compression along cracks - Nazarenko, V.M.; Dovzhik, M.V. (Reports of the National Academy of Sciences of Ukraine, 2017)
A nonclassical problem of fracture mechanics for a material with two parallel coaxial cracks is studied. The axisymmetric problem for a penny-shaped crack is considered. The numerical examination of a case of composite materials is conducted.